Faktor-faktor yang Mempengaruhi Mahasiswa Terhadap Pemilihan Kompetensi di Program Studi Matematika Universitas Udayana - Ida Ayu Putu Ari Utari; Ratna Sari Widiastuti (Jurnal Matematika, 2021)
Tertiary education is a level of education after secondary education; it includes associate program, bachelor program, master program, specialist program, and doctorate program held by a higher educational institution. Through this higher educational institution, the students are taught to be professionals and experts in a certain area of discipline. Universitas Udayana, the oldest university in Bali, is one of the top universities in Indonesia that provides people with a high-quality education. One of the faculties in it is the faculty of mathematics and natural sciences which has six bachelor’s degree study programs, for example, mathematics program. This study program has three competencies, namely computational mathematics, financial mathematics, and statistics. Each competence has its respective applicant and the students have a certain consideration before choosing a certain competence. This study aimed to know the factors affecting the selection of a certain competence in the mathematics program in Universitas Udayana. The data analysis technique used here was the multiple regression analysis by modeling the dependent variables and independent variables. This study found that that the prospect of a certain competence had the most dominant effect on the students’ decision in choosing the competence in the Mathematics program in Universitas Udayana.